PRIORITIES OF THE PEOPLE-ORIENTED APPROACH IN THE ECONOMIC SECURITY MANAGEMENT SYSTEM OF UKRAINE - PRIAMUKHINA, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study draws attention to the issue of ensuring the economic security of the state, but with an eye on the social, in particular, the human-centric aspect of the country’s development. The purpose of the research is to substantiate the priorities of the people-oriented approach in the economic security management system of Ukraine. It is shown that most of the functions and tasks of socially oriented policy are implemented within the framework of guaranteeing the social security of the country, however, it is fair to say that the aspect of people-centeredness is important to extend to other components of the economic security of the state. It was established that the effects of synergy between the economic security of the state and people-centeredness are achieved when important social issues and problems are laid as a basis for ensuring all components of the economic security of the state. According to this approach, the aspect of people-centeredness is actually fundamental in ensuring all components of the economic security of the state. Priorities of state regulation have been identified for all components of the state’s economic security, namely, macroeconomic, financial, foreign economic, investment, innovation-technological, social, demographic, energy, production, and food. Manifestations of insufficiently effective state policy of regulation of social development in Ukraine have been identified. Their negative socio-economic consequences, as well as threats to the economic security of Ukraine, are outlined. It was concluded that at the current stage of the development of the economy of Ukraine, the task of guaranteeing the economic security of the state has significantly intensified and strengthened. Therefore, it is necessary to strengthen the aspects of monitoring and analysis, forecasting and planning, as well as the implementation of measures of a proactive policy of strengthening the stability and stability of the national economic system. At the same time, it should be understood that the central element in the country’s system is a person. Therefore, measures aimed at strengthening economic security must first be checked to see how they affect the parameters of the quality of life and the provision of social services to the population. Moreover, not from the standpoint of negative influence, but in terms of how they will contribute to the improvement of the social sphere of the country.